Fusarium Wilt of Canary Island Date Palm - Monica L. Elliott (EDIS)
As the name implies, Fusarium wilt of Canary Island date palm is primarily observed on the Canary Island date palm. It was first documented in the United States in the 1970s in California, but it was not documented in Florida until 1994. It now occurs throughout the state. The fungus obstructs the xylem (water-conducting) tissue, which results in desiccation and death. This revised 5-page fact sheet was written by Monica L. Elliott, and published by the UF Department of Plant Pathology, August 2012.